Effect of the cBN Content and Sintering Temperature on the Transverse Rupture Strength and Hardness of cBN/DiamondCutting Tools - Kır, Durmuş; Islak, Serkan; Çelik, Halis; Çelik, Ertuğrul (Science of Sintering, 2012)
The aim of this work was to investigate the effect of cBN content and sintering temperature on the transverse rupture strength (TRS) of cBN/diamond cutting tools produced by hot pressing. The segments containing different cBN content were manufactured under 35 MPa pressure at 600, 650 and 700 °C with a 3 minutes sintering time. The TRS of segments were determined using three-point bending test. Microstructure and phase composition of fracture surface of segments were determined by scanning electron microscopy (SEM), and X-ray diffraction (XRD) analysis. The obtained results show that the TRS of the segments with cBN were higher than that of the segments with diamond
Keywords: cBN/diamond cutting tools, Hot-pressing, TRS